Future trends in high‐power bipolar metal‐oxide semi‐conductor controlled power semi‐conductors. Issue 3 (1st May 2014) - Rahimo, Munaf
Abstract : Silicon‐based high‐power devices continue to play an enabling role in modern high‐power systems, especially in the fields of traction, industrial and grid applications. Today, approximately 30 years after its invention, a bipolar‐metal‐oxide semi‐conductor controlled switch referred to as the insulated gate bipolar transistor (IGBT) is the device of choice for the majority of power electronics converters with power ratings ranging from few kWs to beyond the 1 GW mark. Following a brief introduction into power devices and applications in general, this paper will provide an overview of the development history and recent advancements of the IGBT. More importantly the future technology trends purely from the device design view point will be discussed including the predicted performance impact such technology platforms will have at the system level especially in the high‐power range.